2014
DOI: 10.1177/1090820x14545618
|View full text |Cite
|
Sign up to set email alerts
|

The Oncoplastic Reduction Approach to Breast Conservation Therapy: Benefits for Margin Control

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 27 publications
2
39
2
Order By: Relevance
“…Our mean OPD is 31 mm, a condition that has been directly related to higher rates of PMR, RR and CMR but conversely, our rates are in line with reported results for lesions smaller than 15 mm …”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Our mean OPD is 31 mm, a condition that has been directly related to higher rates of PMR, RR and CMR but conversely, our rates are in line with reported results for lesions smaller than 15 mm …”
Section: Discussioncontrasting
confidence: 60%
“…Our mean OPD is 31 mm, a condition that has been directly related to higher rates of PMR, RR and CMR 25-30 but conversely, our rates are in line with reported results for lesions smaller than 15 mm. 31,32 Furthermore, despite several experiences reporting higher rates of PMR, RR, and CMR for DCIS 33,34 or tumors previously treated with NACT 35,36 our study refutes these data.…”
Section: Discussioncontrasting
confidence: 54%
“…In addition, to achieve the desired oncological results, this change may play an important role to get good cosmetic outcomes and improve quality of life in patients (1,2). New innovations are created in the mentioned surgical techniques, emphasizing more on the cosmetic results after surgery through the reconstruction of partial mastectomy, called oncoplastic (3)(4)(5). Different studies showed desirable and appropriate therapeutic results for this method such as good cosmetic outcomes, better control over tumor margin, high satisfaction of patients, and high probability of breast conservation (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] This technique allows for the removal of large amounts of breast tissue, thereby allowing for wider tumor margins while improving cosmetic results. 9,[13][14][15][16][17][18] Patients experience greater improvement in body image satisfaction and larger gains in body image perception. 18,19 They value the aesthetic benefit gained by performing simultaneous bilateral reduction mammoplasty with partial mastectomy.…”
mentioning
confidence: 92%
“…[6][7][8] Additionally, recent studies have shown that oncoplastic surgery allows for improved margin control with lower reexcision rates and lower recurrence rates. 9 Bilateral reduction mammoplasty is a valuable oncoplastic technique in women with preoperative macromastia and patients with large tumor-to-breast ratios. [10][11][12] This technique allows for the removal of large amounts of breast tissue, thereby allowing for wider tumor margins while improving cosmetic results.…”
mentioning
confidence: 99%